Evaluation of Eucalyptus Hybrid Clones with Respect to Pulping and Paper Making Properties - Mahajan, Sushma; Singh, S. V.; Rao, R. V.; Singh, S. P.; Gupta, Pallavi (Indian Forester, 2000)
Three clones of Eucalyptus hybrid were subjected to kraft pulping experiments at 16% total active alkali charge. Four trees of each clone were studied. Pulp yield, screened rejects, kappa number and physical strength properties in terms of tensile index, burst index and tear index were determined after beating the unbleached pulps in PFI mill at constant revolution of 8000. All the trees from these clones possessed adequate pulp yield and strength properties in the following order: Clone B(48.00%) > Clone C(43.71%) > Clone A(42.92%).